Closure - Journal of Infrastructure & Facility Asset Management (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Journal of Infrastructure & Facility Asset ManagementVolume 4, Issue 1, April 2022 (e) ISSN 2656-8896 (P) ISSN 2656-890XJIFAM, Vol.4, Issue 1, April 2022Comparison of Embankment Reinforcement Requirements with Geotextile on Soft Soil with 2D and 3D Slope Stability Analysis Methods Nur Arfiati Shoffiana, Yudhi Lastiasih & Trihanyndio Rendy Satrya Evaluation of Smart Mobility Indicators in Responding COVID-19 Pandemic in Indonesia Shanty Y. Rachmat & Ganesha G. MangkoesoebrotoGeotechnical Mapping for Soil Physical and Mechanical Parameters and Hard Soil Depth in Badung Regency Zefira Wisna Maulidha, Trihanyndio Rendy Satrya & Yudhi LastiasihThe Physical Integration of Smart Transportation Characteristics of Suroboyo Bus and the Feeder Cindy Nur Aziza Rahman, Eko Budi Santoso & Siti NurlaelaThe Adequacy of Public Bus Fleet During the Covid-19 Pandemic (Case of The Transjakarta Corridor 1 DKI Jakarta, Indonesia) Amanda Dian W.Kusumawardani, Ibnu Syabri, Fika Novitasari & Naya C. Drestalita JIFAM, Vol.3, Issue 3, December 2021A New Approach to Estimate the Potential Assets Loss due to Dam-Break Event in Indonesia Farrel Wiguna, Doddi Yudianto, Bobby Minola Ginting & Albert WicaksonoThe Effect of Addition RAP as Quality Improved for Hot Paved Mixtures Irfan Zhain, Ria Asih Aryani Soemitro & Hitapriya SuprayitnoThe Socio-economic Transformations in the Peri-urban of Bandung Metropolitan Area Yanti Budiyantini & Sheilla AlvianyThe spatiotemporal variable effects of individuals' CO2 emission in Bandung Metropolitan Areas Dimas B.E. Dharmowijoyo & Cynthia D. MaharaniManaging the Past into Future: Materiality and Discourse on Cultural LandscapeWijaya Martokusomo Wijaya Martokusumo